Potential of Secang Wood (Caesalpinia sappan L.) Ethanol Extractas Anti-Oxidant and Sun-Protection - Hafshah, Mutista; Rohmah, Alfiatu; Mardliyah, Ana (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2022)
Although sunlight has numerous health benefits, prolonged direct exposure to the sun can be harmful to the skin. Among the negative effects of sun exposure are redness and burning of the skin, as well as dullness, wrinkles, dryness, and premature aging, as well as skin cancer. The use of sunscreen to protect the skin from the harmful effects of prolonged sun exposure is becoming more widespread. On the other hand, some sunscreens contain potentially harmful chemicals such as isopropyl alcohol, DEA (diethanolamine), TEA (triethanolamine), and MEA (monoethanolamine), which can cause allergic reactions as well as kidney and liver disorders when used for an extended period of time. As a result, this investigation was carried out in order to determine the antioxidant potential of natural ingredients, specifically sappan wood (Caesalpinia sappan L.), using the DPPH method, as well as its potential as a sun-protective agent using an in vitro SPF test using ultraviolet-visible (Uv-Vis) spectrophotometry (Uv-Vis). The results revealed that the maceration method produced a 17.779 percent yield of ethanol extract of sappan wood, which was used in this study. The extract possesses extremely potent antioxidant activity, as evidenced by its IC50 value of 12,611 mg/L. Furthermore, based on the results of tests and the calculation of the SPF (sun protection factor) value, sappan wood extract has been shown to have potential as a sun protection agent. Using an extract concentration of 120 mg/L, the highest SPF value.